SOCIO-ECONOMIC PREDICTORS OF LIFE STYLE. A PILOT STUDY - Slachtova, Hana; Tomaskova, Hana; Splichalova, Anna (Biomedical papers, 2003)
In epidemiological studies there exists the evidence of relationship between socio-economic status (SES) and health. The suspicious cause of these differences is life-style. The aim of the presented study was to identify the relationship between SES, demographic characteristics and the life-style in an industrial region. A structured questionnaire was distributed to a random sample of some 3,000 aged 25-70 and collected by postal delivery. The SES and demographic factors being analysed were sex, age, education, marital status and economic situation of the family in the relationship with a wide range of information on life style. The data was analysed using the chi-square test and logistic regression. The total number of analysed questionnaires was 634. The lowest response-rate was in the group with the basic education. Significant differences were found by sex in education (less women with university degree) and household income (more women in the lowest income category, men in the highest one). A detail analysis of the aggregated variables (adjusted for all SES variables) found: passivity and contentment were in adverse correlation with the level of education and economic situation; psychical well-being was correlated with family status and economic situation, risk behaviour was correlated with all SES factors except sex and education. Among the analysed factors economical situation of respondents, family and education were the most significant determinants of the differences in life-style.
Keywords: Socio-economic status/ Life-style/ Risk behaviour/ Activity/ Psychical well-being